Legalitas Transaksi Finansial Penyandang Disabilitas Mental dan Disabilitas Intelektual dalam Perspektif Islam - Ahmad Bahrul Hikam; Mohamad Zaenal Arifin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2023)
This paper discusses the legality of financial transactions carried out by people with mental disabilities and intellectual disabilities. From a social point of view, these two disability groups are part of the members of society who also have rights and obligations that must be recognized. This research uses qualitative literature method. The primary data used are the Qur'an and hadith, while the secondary data is obtained through books of tafsir, books, articles, and others. Data sources are discussed and analyzed in depth to find out about the legality of using property and paying zakat carried out by people with mental disabilities and intellectual disabilities. The results showed that in terms of the legality of financial transactions, these two disability groups are prohibited from using their property, whether their mental or intellectual disorders are permanent or temporary. To assist them in the use of property, access is provided in the form of forgiveness or guardianship. Meanwhile, in the case of zakat harta (maal), people with mental disabilities and intellectual disabilities are still subject to obligations, but the payment of zakat harta is assisted in paying by the guardian.